2019
DOI: 10.1021/jacs.8b12861
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Effects between Hydrophilic Pores and Solvents: Catalytic Consequences of Hydrogen Bonding on Alkene Epoxidation in Zeolites

Abstract: Hydrophobic voids within titanium silicates have long been considered necessary to achieve high rates and selectivities for alkene epoxidations with H2O2. The catalytic consequences of silanol groups and their stabilization of hydrogen-bonded networks of water (H2O), however, have not been demonstrated in ways that lead to a clear understanding of their importance. We compare turnover rates for 1-octene epoxidation and H2O2 decomposition over a series of Ti-substituted zeolite *BEA (Ti-BEA) that encompasses a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
270
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 172 publications
(321 citation statements)
references
References 105 publications
16
270
2
Order By: Relevance
“…Different densities of Brønsted acid H + or Si-OH groups within zeolites stabilize water networks of distinct clustered and extended hydrogen-bonded structures, [43][44][45]75 which have been reported to inuence reactivity in numerous ways, including different competitive adsorption of solvent(s) and reactants, 64,65 entropic gains when water networks are disrupted by transition states, 28,76 and entropic losses when transition states are disrupted by water networks. 34 Thus, interrogation of H-zeolite samples with varying H + and Si-OH density is required to disentangle their separate effects on intrapore solvent structure, prior to relating systematically varying solvent structures to the rate and equilibrium constants of a probe reaction catalyzed by H + sites, such as bimolecular ethanol dehydration to diethyl ether (DEE).…”
Section: Kinetics Of Brønsted Acid-catalyzed Ethanol Dehydration and mentioning
confidence: 99%
See 2 more Smart Citations
“…Different densities of Brønsted acid H + or Si-OH groups within zeolites stabilize water networks of distinct clustered and extended hydrogen-bonded structures, [43][44][45]75 which have been reported to inuence reactivity in numerous ways, including different competitive adsorption of solvent(s) and reactants, 64,65 entropic gains when water networks are disrupted by transition states, 28,76 and entropic losses when transition states are disrupted by water networks. 34 Thus, interrogation of H-zeolite samples with varying H + and Si-OH density is required to disentangle their separate effects on intrapore solvent structure, prior to relating systematically varying solvent structures to the rate and equilibrium constants of a probe reaction catalyzed by H + sites, such as bimolecular ethanol dehydration to diethyl ether (DEE).…”
Section: Kinetics Of Brønsted Acid-catalyzed Ethanol Dehydration and mentioning
confidence: 99%
“…Here, the apparent activation volume is positive because transition states include two adsorbed C 2 H 5 OH molecules while the MARI species only includes one. The disruption of extended hydrogen-bonded networks by transition states has also been implicated in aqueous-phase glucose-fructose isomerization 34 and 1-octene epoxidation catalysis 28 in Ti-Beta zeolites, where zeolites of different hydrophobicity enabled including or excluding H 2 O networks or clusters, but not systematic variation of the intrapore structure of these networks between these two limiting conditions. Here, we have demonstrated that gas-phase kinetic measurements and spectroscopic characterizations with co-fed solvent molecules under conditions that lead to intrapore condensation of extended liquid-like networks enable quantifying the thermodynamic nonidealities introduced by the solvation of kinetically relevant intermediates and transition states within conning environments, which are inaccessible to measurements performed in the liquid phase.…”
Section: Ab Initio Simulation Of Dehydration Transition State Solvatimentioning
confidence: 99%
See 1 more Smart Citation
“…Titanium substituted zeolites with the FAU (1.3 nm supercages), BEA (0.65 nm pores), MFI (0.55 nm pores) frameworks and siliceous CDO (0.45 nm pores) were synthesized through post-synthetic modification 5,39,40 or hydrothermal synthesis 19 to prepare materials with a range of controlled topologies (e.g., 2D pore networks, 3D supercages), mean pore dimensions (0.45 -1.3 nm), and densities of (SiOH) x . Here, we make comparisons primarily among materials that contain the greatest and lowest densities of (SiOH) x (i.e., the most hydrophilic and hydrophobic samples).…”
Section: Spectroscopic and Computational Characterization Of H 2 O Stmentioning
confidence: 99%
“…Φ NMR is calculated as the ratio of the peak area for the Q 3 to the sum of Q 4 and Q 3 sites, and it can quantitatively measure the variation of isolated SiOH on the surface of S-1. [30] From bottom to up in (a) and (b), the reaction time is 0, 1, 5, 30, 60, and 120 min in turns. Obviously, the red shift of the isolated SiOH can be observed while its amount remains unchanged following the reaction time.…”
Section: (4 Of 8)mentioning
confidence: 99%